What Drives Customer Intention in Digital Banking? Evidence from Trust, Security Risk, and Technological Innovation - Yohanes Ferry Cahaya; Alloysius Pamurda Dhika Mahendra; Herni Pujiati; Ilham Nawang Armanda (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study examines the determinants of digital banking adoption intention among Book IV bank customers in Indonesia, focusing on the interplay between trust, security risks, and technological innovation. Using Smart PLS-SEM with data from 385 respondents, we investigate how technological innovation influences customer trust and perceived security risks, which subsequently affect digital banking usage intention. Results reveal that technological innovation significantly enhances trust while reducing security risk perceptions. Trust emerges as the strongest predictor of digital banking intention, while security risks negatively impact adoption. The study contributes theoretical insights into technology acceptance in emerging markets and provides practical implications for banks developing digital transformation strategies in competitive environments.